The effect of cash holdings on financial performance in German and Dutch multinationals - Annika Post (The Central European Review of Economics and Management (CEREM), 2022)
Aim: A global rise in inflation has sparked a renewed interest in the matter of cash holding decisions in firms. Increasing inflation makes for different cash holding practices, but the effect of cash holdings on firm performance remains unclear. This study aims to determine what the effect of higher cash holdings is on financial performance in German and Dutch multinational corporations (MNCs) Design / Research methods: The sample consists of 105 MNCs, 69 of which are from Germany, while 36 firms are Dutch. Through a standard OLS regression, financial performance, measured in return on assets, is regressed on cash holdings, measured in a cash-to-assets ratio. Conclusions / findings: A negative relationship is found between cash holdings and financial performance. This is because agency costs are more considerable when pools of cash become larger. Moreover, the relationship is significantly negative in the German subsample, but not in the Dutch subsample. This could be explained by differences in masculinity in national culture. Originality / value of the article: The effect of cash holdings on firm performance has been neglected in the literature. By focusing on two similar countries, and introducing national culture into the discussion of cash management, the study is valuable to both management and literature. Limitations: Research design is rather limited. Findings are preliminary, and need to be verified through the use of more extensive studies.
Keywords: G30; 330; Cash Holdings; Firm Performance; National Culture